Diversity of Bird Species in the Samarendah Park Area Samarinda City East Kalimantan Province - Muhamad Agil; Raihan Raihan; Syifa Aulia Putri; Dina Firda Safitri; Intan Nur Aini; Melati Melati; Amul Lihan; Cindi Amelia Putri; Firda Latifah Ashari; Titi Windiani; Anisa Tatia Putri (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Every city has parks or green areas which have an important function in creating a healthy and comfortable environment. Samarendah Park, located in the city of Samarinda, is a city park area filled with various types of vegetation such as trees, grass and others. The presence of that vegetation allows various types of birds to come and search for food or build nests. The diversity of bird species in Samarendah Park is not yet known, making it very important to conduct research. The aim of this study is to determine the diversity index of bird species found in Samarendah Park, Samarinda. The method used in this research is Point Count. Each bird species observed at the observation points is noted for its morphology, counted, documented, and identified. The obtained data were analyzed using the Diversity Index (H’), Relative Abundance Index (RAI), Evenness Index, Richness Index, Feeding Guild, and conservation status based on the International Union for Conservation of Nature. (IUCN). The research results obtained 7 types of birds with a diversity index value of 1.36, which falls into the moderate category. The highest IKR value is Passer montanus at 56.03%, the Species Evenness Index value is 0.7, and the Species Richness Index is 1.26. The results of the Feeding Guild analysis revealed 3 types of omnivores, 2 types of insectivores, and 2 types of granivores. As for the conservation status of all the bird species found, they are classified as Least Concern. (LC).